Magnetic core micelles as a nanosorbent for the efficient removal and recovery of three organophosphorus pesticides from fruit juice and environmental water samples. Issue 9 (27th February 2018) - Hamedi, Raheleh; B.G. Aghaie, Ali; Hadjmohammadi, Mohammad Reza
Abstract: Sodium dodecyl sulfate coated amino‐functionalized magnetic iron oxide nanoparticles were used as an efficient adsorbent for rapid removal and preconcentration of three important organophosphorus pesticides, chlorpyrifos, diazinon and phosalone, by ultrasound‐assisted dispersive magnetic solid‐phase microextraction. Fabrication of amino‐functionalized magnetic nanoparticles was certified by characteristic analyses, including Fourier transform infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, and transmission electron microscopy. Affecting parameters on the removal efficiency were investigated and optimized through half‐fractional factorial design and Doehlert design, respectively. The analysis of analytes was performed by high‐performance liquid chromatography with ultraviolet detection. Under the optimum conditions, extraction recoveries for 20 ng/mL of organophosphorus pesticides were in the range of 84–97% with preconcentration factors in the range of 134–155. Replicating the experiment in above condition for five times gave the relative standard deviations <6%. The calibration curves showed high linearity in the range of 0.2–700 ng/mL and the limits of detection were in the range of 0.08–0.13 ng/mL. The proposed method was successfully applied for both removal and trace determination of these three organophosphorus pesticides in environmental water and fruit juice samples.